THE ROLE OF DIGITAL TECHNOLOGIES AND ARTIFICIAL INTELLIGENCE IN EDUCATION - Z.O. Karimova; N.M. Karimov (Uzbekistan Open Conference, 2026)
This study analyzes the impact of AI and digitalization on contemporary educational models. Using methods of systems analysis and expert assessment, the potential of digital platforms for personalizing and automating learning was determined. Alongside the advantages, such as inclusivity and diagnostics, critical risks were identified, including ethical dilemmas and the digital incompetence of staff. The research culminates in recommendations for the ethical integration of AI into pedagogical practice.
Keywords: digitalization of education; artificial intelligence; adaptive learning; personalization; digital competence; educational platforms; machine learning; inclusive education; AI ethics; pedagogical transformation